Aplikasi Mobile Digital Library SMP N 1 Kaliori Kabupaten Rembang - Sartono, Rheznandya Refan; Fachri, Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
SMP Negeri 1 Kaliori is located in Pati Regency. The school library of SMP Negeri 1 Kaliori is a source of knowledge at the school, however, the data processing is still manual which makes it difficult for librarians to manage library data. Therefore, an application-based library information system was created to make it easier for librarians. in managing library data in making library information systems using the Java programming language which is a programming language specifically for making an application, the information presented in this application includes information on borrowing, returns, student data, book status data, book codes, late fines and information book collection. With this application, it can help students borrow and return books easily. Students no longer need to look directly at books in the library. By opening this application, students can see all types of books in the library. This application is also equipped with a fine feature so students who borrow books beyond the specified time period will receive a fine. Students can also see the fine bill in the application.